THE ROLE OF REMITTANCES RECEIVED ON THE POST-COMMUNIST ALBANIA’S FINANCIAL DEVELOPMENT - Genci Gjanci; Ardian Cerava (European Scientific Journal, ESJ, 2014)
Studies on the role of remittances received on the recipient country’s financial development have given mixed results. The most notable empirical studies try to assess this relation for a group of countries using panel data. In this study we concentrate on the relation between these two variables for the post-communist Albania using annual time series data provided by the World Bank. The multiple regression model developed is estimated using the ARDL bounds testing approach which is highly recommended when the sample size is small. Results indicate a significant positive role of remittances in the country’s financial development. In particular, a 10% increase in remittances is associated with approximately a 11.78% increase in the financial development. Other financial development enhancing variables are trade openness and the sum of foreign direct investment and official development assistance, although with a smaller impact.